Bangladesh : Agriculture Insurance Situation Analysis - World Bank Group (World Bank, Washington, DC, 2018)
Agriculture is key in Bangladesh but highly exposed to risks.The Government provides significant support to agriculture, but currently provides limited support to the development of agriculture insurance.While the Government and external donors spend large amounts of money in the aftermath of disasters – average annual costs of disasters are USD 300 million - the funding gap is still high and can reach more than USD 1.5 billion in bad years.In spite of Government’s efforts, credit to agriculture is still constrained and represents 3 percent of total lending.If agriculture insurance programs were to be developed in Bangladesh, the overall legal, regulatory and supervisory insurance environment would require strengthening.Based on this preliminary assessment and discussions with key stakeholders, the WBG will prepare a technical report and policy briefing for Bangladesh Ministry of Finance’s Bank and Financial Institutions Division (BFID) on four potential types of agricultural insurance programs which have been identified through this situational analysis as priority solutions for further investigation. The four priority areas identified for further investigation are: (1) Livestock insurance for commercial dairy farmers and poultry farmers; (2) Insurance cover for shrimp producers and artisanal fishermen; (3) Crop insurance linked to credit for small and marginal cereal farmers; and (4) Fully subsidized flood-index insurance for the most vulnerable rural households. The diagnostic reports will also analyze potential institutional frameworks that could be considered for agricultural insurance in Bangladesh, paying specific attention to the potential roles for the Government and insurers.